Maps: Finding Our Place in the World - Edited by James R Akerman and Robert W Karrow Jr. - WINLOW, HEATHER (Geographical Journal, 2009)
The article reviews the book "Maps: Finding Our Place in the World," edited by James R. Akerman and Robert W. Karrow Jr.